Odpowiedzi

Najlepsza Odpowiedź!
2010-01-08T19:58:48+01:00
1.
... =
= 2(a+b) - 1/2 * (a-b) =
= 2(-4 + 6) - 1/2 * (-4-6)=
= 2 * 2 - 1/2 * (-10) =
= 4 + 5 = 9

2. ...=
= x² - 2² - (9x² + 6x + 1) =
= x² - 4 - 9x² - 6x - 1 =
= -8x² - 6x - 5 =
= -8 * (-2)² - 6 * (-2) - 5 =
= -8 * 4 + 12 - 5 =
= -32 + 7 = -25

3. ... =
= 10x - 5x² - 2 -x + 5x² - x =
= 8x - 2 =
= 8 * 1,6 - 2 =
= 12,8 - 2 = 10,8

4.
... = ...
5(5x + 2) = 3(3x + 6)
25x + 10 = 9x + 18
16x = 8 / : 16
x = 1/2

5. ... = ... / *6
2(2x+1) - 3(3x-2) = 12 - 6x
4x + 2 - 9x + 6 = 12 - 6x
x = 4

6. ...=...
2(x² - 6x +9) - (16 + 8x + x²) = x²-6x
2x² - 12 x + 18 - 16 - 8x - x² = x² - 6x
10x = -2 / :10
x = -0,2